Cultural evolution of killer whale calls:background, mechanisms and consequences - Filatova, Olga A.; Samarra, Filipa I. P.; Deecke, Volker B.; Ford, John K. B.; Miller, Patrick J. O.; Yurk, Harald (Behaviour, 2015)
Cultural evolution is a powerful process shaping behavioural phenotypes of many species including our own. Killer whales are one of the species with relatively well-studied vocal culture. Pods have distinct dialects comprising a mix of unique and shared call types; calves adopt the call repertoire of their matriline through social learning. We review different aspects of killer whale acoustic communication to provide insights into the cultural transmission and gene-culture co-evolution processes that produce the extreme diversity of group and population repertoires. We argue that the cultural evolution of killer whale calls is not a random process driven by steady error accumulation alone: temporal change occurs at different speeds in different components of killer whale repertoires, and constraints in call structure and horizontal transmission often degrade the phylogenetic signal. We discuss the implications from bird song and human linguistic studies, and propose several hypotheses of killer whale dialect evolution.